Święte 11, Feature 1149: Sequence of Funerary Rites Practiced by Corded Ware Peoples and Early Bronze North Pontic Cultures - Kośko, Aleksander; Klochko, Viktor I.; Olszewski, Adam; Włodarczak, Piotr; Goslar, Tomasz (Baltic-Pontic Studies, 2018)
A set of sources embodied by features 1149A and 1149B at Święte 11, Jarosław District, Podkarpackie Province, is one of a kind in Lesser Poland as it includes a vessel associated with steppe cultures of the Northwest Black Sea Coast. The vessel has been discovered in a stratigraphic context that is not fully clear. It probably constituted an offering (trizna) connected with the male burial identified in the niche grave underneath. The vessel appears to be linked to the late Yamnaya/early Catacomb horizon. Such chronological attribution is further supported by an absolute date of the 2nd half of the third millennium BC established for bones. The vessel sits alongside other finds that provide corroboration for connections the population of the younger Corded Ware phase in Lesser Poland had with eastern European regions.